Characterization of Coxsackievirus A6- and Enterovirus 71-Associated Hand Foot and Mouth Disease in Beijing, China, from 2013 to 2015 - Li, Jie; Sun, Ying; Du, Yiwei; Yan, Yuxiang; Huo, Da; Liu, Yuan; Peng, Xiaoxia; Yang, Yang; Liu, Fen; Lin, Changying; Liang, Zhichao; Jia, Lei; et al. (Frontiers in Microbiology, 2016)
Background: Etiology surveillance of Hand Foot and Mouth disease (HFMD) in Beijing showed that Coxsackievirus A6 (CVA6) became the major pathogen of HFMD in 2013 and 2015. In order to understand the epidemiological characteristics and clinical manifestations of CVA6-associated HFMD, a comparison study among CVA6-, EV71- (Enterovirus 71) and CVA16- (Coxsackievirus A16) associated HFMD was performed. Methods: Epidemiological characteristics and clinical manifestations among CVA6-, EV71- and CVA16-associated mild or severe cases were compared from 2013 to 2015. VP1 gene of CVA6 and EV71 from mild cases, severe cases were sequenced, aligned and compared with strains from 2009 to 2015 in Beijing and strains available in GenBank. Phylogenetic tree was constructed by neighbor-joining method. Results: CVA6 became the predominant causative agent of HFMD and accounted for 35.4% and 36.9% of total positive cases in 2013 and 2015, respectively. From 2013 to 2015, a total of 305 severe cases and 7 fatal cases were reported. CVA6 and EV71 were responsible for 57.5% of the severe cases. Five out six samples from fatal cases were identified as EV71. High fever, onychomadesis and decrustation were the typical symptoms of CVA6-associated mild HFMD. CVA6-associated severe cases were characterized by high fever with shorter duration and twitch compared with EV71-associated severe cases which were characterized by poor mental condition, abnormal pupil and vomiting. Poor mental condition, lung wet rales, abnormal pupil and tachycardia were the most common clinical features of fatal cases. The percentage of lymphocyte in CVA6-associated cases was significantly lower than that of EV71. High percentage of lymphocyte and low percentage of neutrophils were the typical characteristics of fatal cases. VP1 sequences between CVA6- or EV71-associated mild and severe cases were highly homologous. Conclusion: CVA6 became one of the major pathogens of HFMD in 2013 and 2015 in Beijing. Epidemiological characteristics, clinical manifestations of CVA6-, EV71- and CVA16-associated cases in this study enriched the definition of HFMD caused by different pathogens and shed light to accurate diagnosis, appropriate treatment and effective prevention of HFMD.